Trade Finance in A Liquidity Crisis - Ellingsen, Tore (The World Bank, 2009)
The paper discusses the reasons for supporting international trade finance during a liquidity crisis. Targeted interventions are justified when prices are rigid and sellers insist on immediate payment due to fears of strategic default. In this case, buyers who reject the seller's offer fail to internalize the seller's benefit from additional liquidity. A general infusion of credit will not facilitate the beneficial transaction, but an infusion targeted at the buyer's bank's trade finance supply will do so. Since there is a need for interventions in one country to benefit actors in another, international coordination is called for